PEMANFAATAN KOMPOSIT ENCENG GONDOK DAN SERABUT KELAPA SEBAGAI BAHAN INSULASI PADA KOTAK PENDINGIN IKAN (COOLBOX) - Aurista Miftahatul Ilmah Aurista; Triyanti Irmiyana; Moh. Irfan (Prodi Fisika FST UNJA, 2021)
The quality of freshness of fish caught by traditional fishermen must be maintained, one way is by adding coolbox insulation so that it can insulate heat on fishing boats. So far, fishermen use sterofoam as a temperature barrier to maintain the freshness of the fish. The use of sterofoam can pollute the environment. In this research, water hyacinth composite fiber and coconut fiber are used to manufacture coolbox insulation to replace sterofoam as a coolbox insulation material on fishing boats. Water hyacinth powder and dry coconut fibers are mixed into polyurethane with a mass percentage of 40% and 50% which will be compared with pure polyurethare, testing is then carried out to obtain the lowest temperature time and temperature data. The test results show that the percentage of 60% polyurethane and 40% of water hyacinth powder and coconut fiber has an insulation power closer to pure polyurethane with a resistance time of 690 minutes with the lowest temperature of -3 ° C.